Advertising and Content Differentiation: Evidence from YouTube - Anna Kerkhof (ZBW - Leibniz-Informationszentrum Wirtschaft, 2019)
Does advertising revenue increase or diminish content differentiation in media markets? This paper shows that an increase in the technically feasible number of ad breaks per video leads to an increase in content differentiation between several thousand YouTube channels. I exploit two institutional features of YouTube's monetization policy to identify the causal effect of advertising on the YouTubers' content choice. The analysis of around one million YouTube videos shows that advertising leads to a twenty percentage point reduction in the YouTubers' probability to duplicate popular content, i.e., content in high demand by the audience. I also provide evidence of the economic mechanism behind the result: popular content is covered by many competing YouTubers; hence, viewers who perceive advertising as a nuisance could easily switch to a competitor if a YouTuber increased her number of ad breaks per video. This is less likely, however, when the YouTuber differentiates her content from her competitors.
Keywords: D22; L15; L82; L86; 330; advertising; content differentiation; economics of digitization; horizontal product differentiation; long tail; media diversity; user-generated content; YouTube